Delta-Like Factor 1 Negatively Regulates Angiogenesis as a Target Gene of MIR-126-5P after Indirect Revascularization Surgery in Patients with Moyamoya Disease - Lt Col Ayyaz Hussain Awan Ti(M), Hussnain Mohammad Buksh, Ali Zain Ul Abidin (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Moyamoya disease (MMD) is a chronic cerebral hypoperfusion state with increased narrowing of the intracranial internal carotid artery. Objectives: The main objective of the study is to analyses the delta-like factor 1 negatively regulates angiogenesis as a target gene of miR-126-5p after indirect revascularization surgery in patients with moyamoya disease. Material and methods: This retrospective study was conducted in Akhtar Saeed Medical College Lahore during 2020 to 2021. First, we compared the DLK1 expression in DM tissues from patient with moyamoya disease (n = 8) and unruptured aneurysms (n = 8, control group). DM samples (1.0 × 0.5 cm) were collected from patients with moyamoya disease during revascularization procedures. DM samples were harvested from the temporal part of the head and stored for further use. Results: EPC markers CD31, VE-cadherin, and VEGFR-2 were strongly expressed in cultured cells, while hematopoietic marker CD133 did not display remarkable expression, suggesting highly purified EPC isolation. Practical implication: This study will be helpful in EC proliferation and angiogenesis. Conclusion: It is concluded that DLK1, a target gene of miR-126-5p, negatively regulates EC proliferation and angiogenesis and that downregulating DLK1 expression potentially promotes angiogenesis in chronically ischaemic brains. Keywords: DLK1, EC, Proliferation, Angiogenesis